COMMODIFICATION OF TELAJAKAN AT UBUD VILLAGE, GIANYAR, BALI - Brata, Ida Bagus (E-Journal of Cultural Studies; Volume 7, Number 1, February 2014, 2014)
This study was intended to understand the phenomenon of the commodification of telajakan at Ubud Village, Gianyar Regency, Bali in the era of globalization. It focused on how the commodification of telajakan took place in the era of globalization; what factors causing the commodification of telajakan to take place; and what were the impact and meaning of the commodification of telajakan at Ubud Village. The data were collected through observation, interview, library research and documentation study. The theory of Commodification, the theory of Discourse, the theory of Power and Knowledge, and the theory of Globalization were eclectically used in the present study.   The results of the study were as follows. The commodification of telajakan was defined as how it was produced as economic space, how it was distributed through printed media, announcement board, from mouth to mouth, and through the meetings held by traditional organizations, and then it was consumed by the owners and others undertaking businesses. The factors contributing to the commodification of telajakan were market ideology, business of tourism, technological flow, and mass media as the popular cultural agent, mimicry, and economic libido. For the sake of money, telajakan was not regarded as a local genius any longer; its value as traditional green open space was neglected; as a result, ecological damage could not be avoided; the aesthetics of the Balinese architecture was getting extict; and the Balinese identity was getting  destructed.
Keywords: tourism, commodification, telajakan, globalization.